2013
DOI: 10.1177/026248931303200403
|View full text |Cite
|
Sign up to set email alerts
|

New Class of Brominated Polymeric Flame Retardants for use in Polystyrene Foams

Abstract: Flame retardant producers and end users are continually looking for more sustainable solutions through innovation in their customer offerings. Successful solutions need to satisfy a range of characteristics, from processing to technical and environmental performance, which sometimes conflict. This paper covers a new class of brominated polymeric flame retardants designed and developed by The Dow Chemical Company for use in polystyrene foam to meet existing fire and use requirements and have an improved environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…In reaction to these legal developments, alternatives for HBCDD were developed in order to replace HBCDD in PS foam for building and construction applications (Environmental Protection Agency (EPA), 2014). The highest market potential is attributed to a special polymeric brominated flame retardant (PolyFR) (Beach et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In reaction to these legal developments, alternatives for HBCDD were developed in order to replace HBCDD in PS foam for building and construction applications (Environmental Protection Agency (EPA), 2014). The highest market potential is attributed to a special polymeric brominated flame retardant (PolyFR) (Beach et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Following this screening protocol Dow's new class of polymeric FR's, PolyFR, was developed which exhibits a superior environmental profile to that of HBCD and other lower molecular weight FR molecules. The brominated polymer flame retardant is based on a copolymer of styrene and butadiene [3,4]. Typically, a styrene-butadiene-styrene (SBS) triblock architecture is utilized that is brominated on the polybutadiene portion.…”
Section: Technical Performancementioning
confidence: 99%
“…[27][28][29] Therefore, the ame retardants which has high efficiency and low addition still need to be researched for meeting requirements for foaming properties. Recently, as in Scheme 1 a kind of brominated polymer ame retardant (PolyFR) which exhibits better environmental friendliness than that of HBCD was reported, [30][31][32] in which only 3-5 wt% PolyFR in PS or PS foam can exert excellent ame-retardant effect. 33 Mark W. Beach has studied on the mechanism of ame retardant of PolyFR and found that PolyFR has the similar ame retardant mechanism to HBCD in PS blends where both produce hydrogen bromide (HBr) to exert ame retardant effect in gas phase and both produce enhanced degradation of polymers as another important way to exert ame retardant effect in condensed phase.…”
Section: Introductionmentioning
confidence: 99%
“…What's more, PolyFR was an environmentally sustainable alternative to HBCD which has been demonstrated by the environmental health and safety (EH&S) evaluation. 30 The physical chemical properties of PolyFR, namely its high molecular weight, indicated it would possess very low bioavailability and intrinsic toxicity. The results of the environmental fate and ecological toxicity testing demonstrated that PolyFR does not pose the health and environmental issues, such as bioaccumulation and toxicity, which are associated with HBCD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation